Effectiveness of vertical ridge augmentation interventions: A systematic review and meta‐analysis - Urban, Istvan A.; Montero, Eduardo; Monje, Alberto; Sanz‐Sánchez, Ignacio (Journal of clinical periodontology, 2019)
Aim The primary aim of this systematic review was to evaluate the effect of various techniques used for vertical ridge augmentation on clinical vertical bone gain. Material and Methods A protocol was developed to answer the following focused question: “In patients with vertical alveolar ridge deficiencies, how effective are different augmentation procedures for clinical alveolar ridge gain?” Randomized and controlled clinical trials and prospective and retrospective case series were included, and meta‐analyses were performed to evaluate vertical bone gain based on the type of procedure and to compare bone gains in controlled studies. Results Thirty‐six publications were included. Results demonstrated a significant vertical bone gain for all treatment approaches (n = 33; weighted mean effect = 4.16 mm; 95% CI 3.72–4.61; p < 0.001). Clinical vertical bone gain and complications rate varied among the different procedures, with a weighted mean gain of 8.04 mm and complications rate of 47.3% for distraction osteogenesis, 4.18 mm and 12.1% for guided bone regeneration (GBR), and 3.46 mm and 23.9% for bone blocks. In comparative studies, GBR achieved a significant greater bone gain when compared to bone blocks (n = 3; weighted mean difference = 1.34 mm; 95% CI 0.76–1.91; p < 0.001). Conclusions Vertical ridge augmentation is a feasible and effective therapy for the reconstruction of deficient alveolar ridges, although complications are common.